The Efficacy of N-Butylphthalide and Dexamethasone Combined with Hyperbaric Oxygen on Delayed Encephalopathy After Acute Carbon Monoxide Poisoning - Zhang J; Guo Y; Li W; Li G; Chen Y (Dove Medical Press, 2020)
Jiefang Zhang,1 Yuewen Guo,2 Wenyao Li,1 Guangli Li,3 Yankun Chen4 1Intensive Care Unit, Heze Municipal Hospital, Heze City, Shandong Province, People’s Republic of China; 2Emergency Department, Heze Municipal Hospital, Heze City, Shandong Province, People’s Republic of China; 3Department of Pharmacy, Heze Municipal Hospital, Heze City, Shandong Province, People’s Republic of China; 4Department of Neurology, Heze Municipal Hospital, Heze City, Shandong Province, People’s Republic of ChinaCorrespondence: Yankun ChenDepartment of Neurology, Heze Municipal Hospital, 2888 Caozhou Road, Heze City 274000, Shandong Province, People’s Republic of ChinaEmail kundan@126.comBackground: Carbon monoxide (CO) poisoning is a common health problem among people in many countries, primarily because of its severe clinical effects and high toxicological morbidity and mortality. Acute brain injury and delayed encephalopathy after acute carbon monoxide poisoning (DEACMP) are the most common neurological complications. This study was performed to assess the efficacy of N-butylphthalide (NBP) and dexamethasone (DXM) combined with hyperbaric oxygen (HBO) in patients with DEACMP.Patients and Methods: A total of 171 patients with DEACMP were recruited and assigned to the combined therapy group (receiving NBP and DXM 5 mg/day plus HBO therapy) or the control group (HBO therapy as monotherapy). Conventional treatments were provided for all patients. The cognition and movement changes in patients were evaluated by the Mini-Mental State Examination (MMSE), the Montreal Cognitive Assessment (MoCA) scale and the Barthel index of activities of daily living (ADL) before and after the treatment at 1 month, 3 months, and 1 year, respectively.Results: At 1 month, 3 months, and 1 year after the treatment, the MMSE, MoCA and ADL scores were all significantly higher in the combined therapy group than those in the control group. There were no significant alterations in blood glucose, blood lipids, or liver and kidney function during the whole treatment session. Some patients experienced loss of appetite, mild headache and minor skin irritations. However, these patients recovered by themselves and needed no additional medications or special treatment.Conclusion: These results indicated that NBP and DXM combined with HBO for the treatment of DEACMP can significantly improve the cognitive and motor functions of patients and is very safe.Keywords: butylphthalide, NBP, dexamethasone, DXM, hyperbaric oxygen, HBO, DEACMP, carbon monoxide poisoning